A holistic study on the use of blockchain technology in CPS and IoT architectures maintaining the CIA triad in data communication - Bhattacharjya, Aniruddha (Zielona Góra: Uniwersytet Zielonogórski)
Blockchain-based cyber-physical systems (CPSs) and the blockchain Internet of things (BIoT) are two major focuses of the modern technological revolution. Currently we have security attacks like distributed denial-of-service (DDoS), address resolution protocol (ARP) spoofing attacks, various phishing and configuration threats, network congestion, etc. on the existing CPS and IoT architectures.
Keywords: CPS; BIoT; blockchain; IIoT; DDoS; ARP spoofing; M2M; P2P; CIA triad